2022
DOI: 10.1038/s41467-022-30340-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous immunization with inactivated vaccine followed by mRNA-booster elicits strong immunity against SARS-CoV-2 Omicron variant

Abstract: The recent emergence of the Omicron variant has raised concerns on vaccine efficacy and the urgent need to study more efficient vaccination strategies. Here we observed that an mRNA vaccine booster in individuals vaccinated with two doses of inactivated vaccine significantly increased the plasma level of specific antibodies that bind to the receptor-binding domain (RBD) or the spike (S) ectodomain (S1 + S2) of both the G614 and the Omicron variants, compared to two doses of homologous inactivated vaccine. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(105 citation statements)
references
References 55 publications
14
91
0
Order By: Relevance
“…Consistent with data demonstrated by other groups [ 6 , 9 , 11 , 15 , 16 ], we also found that two doses of either mRNA or viral inactivated vaccines had poor levels of neutralizing antibodies against the Omicron variant when assessed between 3–6 months after the second dose of vaccine (Group 1, median 16.00% [IQR 11.97–30.98%]; Group 2, median 26.50% [IQR 23.55–32.05%]; Group 3, median 16.90% [IQR 10.06–24.50%]; and Group 4, median 25.84% [IQR 13.30–32.63%]).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with data demonstrated by other groups [ 6 , 9 , 11 , 15 , 16 ], we also found that two doses of either mRNA or viral inactivated vaccines had poor levels of neutralizing antibodies against the Omicron variant when assessed between 3–6 months after the second dose of vaccine (Group 1, median 16.00% [IQR 11.97–30.98%]; Group 2, median 26.50% [IQR 23.55–32.05%]; Group 3, median 16.90% [IQR 10.06–24.50%]; and Group 4, median 25.84% [IQR 13.30–32.63%]).…”
Section: Resultssupporting
confidence: 93%
“…This finding is similar to a study by Perez-Then et al (2022), who did not detect neutralizing antibodies against the Omicron variant in individuals who received two doses of Coronavac but found a 1.4-fold increase in neutralization activity against Omicron in individuals who received two doses of CoronaVac followed by a booster with BNT162b2 compared to individuals who received two doses of mRNA vaccine [ 15 ]. This is also corroborated by another study by Zuo et al (2022), who observed increases in antibodies that can bind the RBD of VOCs, including Delta (8-fold) and Omicron (14-fold), in 13 individuals who received an mRNA booster after a two-dose regimen of inactivated virus vaccine [ 16 ]. In our current study, we found that the median Omicron RBD-specific IgG1 levels robustly increased by approximately 17–19-fold in individuals approximately one month after receiving an mRNA booster following two doses of mRNA or inactivated virus priming vaccination.…”
Section: Discussionsupporting
confidence: 72%
“…In in-vitro studies, mRNA vaccines have shown higher titers of antibodies and virus neutralisation against VOCs in comparison with an inactivated vaccine. 32 In this way, the decrease in VE in children observed in our study during the Omicron period might have also been secondary to the type of vaccine administered. Additionally, early waning immunity might also be contributing to the decline of the protection.…”
Section: Discussionmentioning
confidence: 65%
“…Higher humoral immune responses as determined by antispike-antibody determinations and sVNT tests have been reported for boostered vaccinees by several studies (15)(16)(17)(18)(19)(20). Additionally, a higher immune response in boostered vaccinees compared to individuals, who only have been vaccinated twice, against the Omicron variant, which nevertheless is weaker than against the wild type virus, has been reported as well (21,22).…”
Section: Discussionmentioning
confidence: 76%